Competing interests and change within the pharmacy education system in South Africa - Allan, Lucie (Rhodes University, Faculty of Pharmacy, Pharmacy, 2006)
This thesis provides a historical account of the emergence of the pharmacy education system in South Africa, and an analysis of the influence of competing interest groups over the pharmacy education curriculum. It provides a critical evaluation of structural-consensus and micro-interpretive approaches to medical and pharmacy education, and sets out a macrointerpretive account of pharmacy education in South Africa. Following Margaret Archer (1979) it analyzes three forms of negotiation between competing interest groups in their efforts to change the pharmacy curriculum; these are political manipulation, external transaction and internal initiation. The thesis argues that whilst the private sector interest group (comprising of retail, wholesale and manufacturing pharmacy) dominated the pharmacy education system until 1994, since then a newly emerged government interest group has begun to compete for educational control. The priorities pursued by this interest group have consistently reflected the objectives set out in the ANC National Health Plan of 1994. The thesis maintains that given its frustration over the non-implementation of the ANC's health policy objectives, the government interest group is likely to resort to direct political manipulation by passing legislation to alter the content of the current pharmacy curriculum. Such changes would seek to ensure that the syllabus more accurately reflects the ANC Plan's community health and primary health care objectives. The thesis asserts that such an outcome (of direct political manipulation of the curriculum) is not inevitable, and can be avoided through a process of internally initiated change. It presents the findings of an interpretive case study into how the Rhodes University Community Experience Programme (CEP) influenced final year pharmacy students' perceptions of the role of the pharmacist. The students' comments were collected by means of focus group interviews, participant observation and documentary analysis. Whilst the CEP did not successfully transform their concept of the pharmacist's role, it did succeed in influencing students' understanding of the notions of community pharmacy and primary health care in line with the government interest group's health objectives. This thesis concludes that internally initiated change within the pharmacy education system, would be preferable to that imposed through external political manipulation, as such change would be more likely to preserve the independent professional interests of pharmacy academics.
Keywords: Pharmacy -- South Africa; Pharmacy -- Study and teaching -- South Africa; Pharmacy -- Practice -- South Africa; Community pharmacy services -- South Africa; Community health services -- South Africa